2019
DOI: 10.1159/000494363
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Clinical Picture of Renal Cell Carcinoma: A Population-Based Study from Helsinki

Abstract: Background: There is a lack of detailed population-based data for renal cell carcinoma (RCC). Objectives: The study aimed to examine the contemporary changes in the clinical picture and treatment of RCC. Methods: A total of 1,719 consecutive patients living in the Helsinki metropolitan area with a solid or cystic renal mass (Bosniak 3–4) ≥10 mm were identified. Data from medical records was evaluated for clinical characteristics and treatments in the periods I (2006–2008), II (2009–2011), III (2012–2014), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Active surveillance has become an option for cystic renal masses in recent years. In a recent study, Erkkilä et al [15] showed that active surveillance for renal masses increased from 8 to 23% between 2006 and 2016. Although it is not routinely recommended, there are several ongoing and published studies about this topic [3-5, 16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Active surveillance has become an option for cystic renal masses in recent years. In a recent study, Erkkilä et al [15] showed that active surveillance for renal masses increased from 8 to 23% between 2006 and 2016. Although it is not routinely recommended, there are several ongoing and published studies about this topic [3-5, 16, 17].…”
Section: Discussionmentioning
confidence: 99%